2021
DOI: 10.3390/ijms22147682
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PI3K/AKT and MAPK Signaling Pathways in Erythropoietin Signalization

Abstract: Erythropoietin (EPO) is a glycoprotein cytokine known for its pleiotropic effects on various types of cells and tissues. EPO and its receptor EPOR trigger signaling cascades JAK2/STAT5, MAPK, and PI3K/AKT that are interconnected and irreplaceable for cell survival. In this article, we describe the role of the MAPK and PI3K/AKT signaling pathways during red blood cell formation as well as in non-hematopoietic tissues and tumor cells. Although the central framework of these pathways is similar for most of cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 131 publications
3
38
0
1
Order By: Relevance
“…We also found that EPOR-interacting proteins include JAK2, EPO, and STAT5A/B, MAPK1/3, which fully suggests that EPOR interacts with EPO and is closely related to the activation of JAK2, STAT5, and MAPK (3,4,6). EPOR is associated with numerous diseases such as urological disorders, musculoskeletal or connective tissue disorders, immune system disorders, endocrine system disorders, hematologic disorders, cancer, or benign tumors, reflecting its broad distribution, and it plays a key role in the human body.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…We also found that EPOR-interacting proteins include JAK2, EPO, and STAT5A/B, MAPK1/3, which fully suggests that EPOR interacts with EPO and is closely related to the activation of JAK2, STAT5, and MAPK (3,4,6). EPOR is associated with numerous diseases such as urological disorders, musculoskeletal or connective tissue disorders, immune system disorders, endocrine system disorders, hematologic disorders, cancer, or benign tumors, reflecting its broad distribution, and it plays a key role in the human body.…”
Section: Discussionsupporting
confidence: 62%
“…Upon EPO stimulation, binding to its homologous dimer receptor complex induces the activation of Janus kinase 2 (JAK2), a non-receptor tyrosine kinase ( 3 ). Activation of JAK2 results in the activation of specific downstream effectors, such as STAT1, STAT3, and STAT5 ( 4 ); the signal transducer and activator of transcription 5 (STAT5) usually refers to STAT5A and STAT5B proteins ( 5 ) and thus activates phosphatidylinositol 3-kinase (PI3K), protein kinase B (AKT), mitogen-activated protein kinase (MAPK), and extracellular signal-regulated kinase 1/2 (ERK1/2) ( 6 , 7 ). EPOR was originally discovered and described in erythroid progenitor cells, but it is also present in non-hematopoietic cells (tissues, organs) such as adipose tissue ( 8 ), bone progenitor cells ( 9 ), neurons ( 10 ), endothelial cells ( 11 ), and intestinal tract ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two major cell survival pathways that are upregulated and activated in lung cancer tissues are mediated by Akt and ERK1/2, which are known to play a crucial role in the regulation of cellular proliferation, differentiation, and migration [22]. Hence, we performed a study of the possible role of lncCDH5-3:3 in the regulation of lung cancer cell proliferation via the Akt-and ERK1/2-mediated signaling pathways.…”
Section: Effects Of Lnccdh5-3:3 Overexpression On Cell Cycle Cell Pro...mentioning
confidence: 99%
“…Tyrosine phosphorylation plays a pivotal role in EPOR signal transduction and the activation of downstream signaling cascades involved in erythropoiesis, including the signal transducer and activator of transcription 5 (STAT5), phosphatidylinositol 3-kinase (PI3K) and mitogenactivated protein kinase (MAPK/ERK) pathways [58][59][60]. The key players of EPO-EPOR signal transduction have been recently reviewed and are presented in Figure 2 [61,62]. Abnormally increased or prolonged activation of the three pathways is implicated in deregulated erythropoiesis and overproduction of red blood cells in polycythemia vera and congenital erythrocytosis [59], wherein inherited mutations in the EPOR itself (ECYT1), and acquired mutations in JAK2 (PV) are already well known genetic causes [1,63].…”
Section: Signal Transduction: Epo-epor Pathwaymentioning
confidence: 99%
“…Black line indicates transition (Figure was created using SMART servier medical art[18]. Figure adapted from[61,62]).…”
mentioning
confidence: 99%